Low flow low gradient aortic stenosis: clinical pathways - I. Sathyamurthy; K. Jayanthi (Indian Heart Journal, 2014)
Aortic stenosis patients with severe LV dysfunction and low cardiac output present with relatively low transvalvular gradients. It is difficult to distinguish them from aortic sclerosis and LV dysfunction with low cardiac output. The former condition is severe AS with LV dysfunction and latter is primarily a contractile dysfunction. Dobutamine stress echocardiogram is key to diagnosis. AS with LV dysfunction associated with preserved contractile reserve benefit from valve replacement and those without contractile reserve needs critical evaluation on a case to case basis. Patients of AS with LV dysfunction with associated coronary artery disease need coronary angiograms to decide regarding need for valve replacement with bypass surgery. A subset of AS patients have low flow, low mean gradients with preserved ejection fraction in whom one must evaluate global hemodynamic load to assess ventriculo-arterial impedence. In this review an approach to the clinical pathways for assessment of low flow, low gradient aortic stenosis has been discussed.